PENGARUH SOSIALISASI PRODUK TABUNGAN BANK SYARIAH DALAM MENINGKATKAN MINAT MASYARAKAT MENABUNG DI KELURAHAN SITIREJO 1 KECAMATAN MEDAN KOTA - Intan Permata Sari Simanjuntak; Eli Agustami; Ismail (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the impact of the socialization of Bank Syariah savings products on people's interest in saving in Sitirejo I Village, Medan Kota District. The background of this research is based on the low understanding and interest of some people in Sharia Bank savings products, so socialization efforts are needed to increase public knowledge and interest in using Islamic banking products. The research uses a quantitative approach with a pre-experimental type of research. The research population was 2,200 people and a sample of 100 respondents was determined using simple random sampling techniques. Data collection was carried out through a questionnaire with a Likert scale which was then analyzed using the help of SPSS version 26 through validity, reliability, normality, multicollinearity, Ftest, t-test, and determination coefficient (R²). The results of the study show that the socialization variable of Sharia Bank savings products has a positive and significant effect on people's interest in saving. This is evidenced by the results of the t-test which shows a calculated t-value of 20.744 with a significance level of 0.000 smaller than 0.05. In addition, the results of the F test showed an F value of 430.307 with a significance level of 0.000 so that the research model was declared feasible. The value of the determination coefficient (R²) of 0.815 shows that the socialization of Bank Syariah savings products is able to explain the public's interest in saving by 81.5%, while the remaining 18.5% is influenced by other factors outside the study. Thus, it can be concluded that the better the socialization carried out, the higher the public's interest in saving at Sharia Banks.